2019
DOI: 10.12998/wjcc.v7.i6.753
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with hysteroscopy for infertility due to isthmocele and hydrometra secondary to cesarean section: A case report

Abstract: BACKGROUND An isthmocele is a scar defect in the uterine wall due to a cesarean section. Its prevalence is unknown, but it has been associated with secondary infertility. Here, we present a case where the patient suffered from an isthmocele that was associated with persistent hydrometra, which developed during in vitro fertilization. CASE SUMMARY The patient underwent hysteroscopic surgery, which successfully resolved the isthmocele as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Loṕez Rivero etal. (25) reported that an isthmocele due to a cesarean section was also associated with persistent hydrometra. In addition, abnormal development of the urogenital tract has been reported to be a cause of hydrometra (26).…”
Section: Discussionmentioning
confidence: 99%
“…Loṕez Rivero etal. (25) reported that an isthmocele due to a cesarean section was also associated with persistent hydrometra. In addition, abnormal development of the urogenital tract has been reported to be a cause of hydrometra (26).…”
Section: Discussionmentioning
confidence: 99%
“…C-section scar defect repairs using minimally invasive approaches are reported to be efficient in achieving reduced clinical symptoms and restore secondary infertility (Gubbini et al, 2011;. López Rivero et al (2019) reported a clinical case of secondary infertility, due to a scar defect with persistent hydrometra that was hysteroscopically corrected to restore fertility. Istvan et al (2017) demonstrated that 80% of the patients diagnosed with a C-section scar defect that had surgical treatments (hysteroscopic and laparoscopic isthmoplasty) became pregnant within 24 months and delivered before 36 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria were as follows: (1) the patients had a history of uterine surgery, and the results of pregnancy ultrasonography met the diagnostic criteria of scarred uterus in Obstetrics and Gynecology [13]; (2) the patients had clear indications of C-section or failed in trail delivery for scarred uterus; (3) the patients were cases of singleton pregnancy; (4) the patients were treated in our hospital throughout the entire process, and no situations such as death, transferring to another hospital, or discontinuation of treatment occurred. Exclusion criteria were as follows: (1) the patients could not communicate with others due to hearing disorders, language disorders, unconsciousness, or mental diseases; (2) the patients quit the treatment, died, changed the treatment regimen, or went missing in follow-up visits; (3) the patients were cases of multiple pregnancy; (4) the intrauterine growth was abnormal with the presence of severe eclampsia, placental adherence, or placenta praevia; (5) the patients had combined liver, kidney, heart and brain dysfunction, pelvic infection, coagulation disorders, or other severe pregnancy complications; (6) the patients had subarachnoid space tissue contraindication; (7) the patients had nipple abnormality; (8) the patients were allergic to the drugs involved in the study.…”
Section: Recruitment Of Study Objectsmentioning
confidence: 99%
“…Compared with nonscarred uterus, the possibility of the previously mentioned complications in patients with scarred uterus undergoing secondary C-section is significantly increased [ 6 ]. A large number of studies show that scarred uterus is a risk factor for complications such as postpartum hemorrhage, which is the primary cause of postoperative death in patients undergoing C-section [ 7 , 8 ]. Although the consensus of secondary vaginal trial delivery of scarred uterus has appeared in recent years, many patients with scarred uterus still prefer C-section [ 9 ], and therefore, rational application of drug treatment to reduce the incidence of postoperative complications is an important measure to guarantee the health of mothers and infants.…”
Section: Introductionmentioning
confidence: 99%